2014
DOI: 10.1155/2014/207268
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Risk of Metabolic Syndrome Based on an Artificial Intelligence Model

Abstract: Metabolic syndrome is worldwide public health problem and is a serious threat to people's health and lives. Understanding the relationship between metabolic syndrome and the physical symptoms is a difficult and challenging task, and few studies have been performed in this field. It is important to classify adults who are at high risk of metabolic syndrome without having to use a biochemical index and, likewise, it is important to develop technology that has a high economic rate of return to simplify the comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 35 publications
(47 reference statements)
0
21
0
Order By: Relevance
“…Hirose et al applied ANN for prediction of the 6-year incidence of MetS by using clinical data [30]. Chen et al concluded that ANN is preferable to the traditional logistic regression analysis for assessing the risk of MetS from sex, age, BMI, waist circumference, waist-to-height ratio, hip circumference, systolic and diastolic blood pressure [31]. Darko Ivanovic´ proposed the feed-forward ANN with back propagation as the training algorithm to predict MetS.…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…Hirose et al applied ANN for prediction of the 6-year incidence of MetS by using clinical data [30]. Chen et al concluded that ANN is preferable to the traditional logistic regression analysis for assessing the risk of MetS from sex, age, BMI, waist circumference, waist-to-height ratio, hip circumference, systolic and diastolic blood pressure [31]. Darko Ivanovic´ proposed the feed-forward ANN with back propagation as the training algorithm to predict MetS.…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…Chen et al [38] proposed a neural network to diagnose the Metabolic Syndrome without using biochemical variables such as blood glucose and cholesterol levels. The authors proposed instead the use of anthropometric variables such as Sex, Age, BMI, WC, HC, WHR, SBP, and DBP, and in an implicit way, they used Weight and Height to measure the occurrence of the Metabolic Syndrome.…”
Section: Reviewmentioning
confidence: 99%
“…This phase conducted experiments using the variables and techniques proposed in the analyzed works by Kroon [36], Ivanovic [22], and Chen [38]. The purpose was to build their performance indicators for the dataset of the population of the Atlantic coast of Colombia.…”
Section: Experimenting With Modelsmentioning
confidence: 99%
See 2 more Smart Citations